Working life and human capital investment: Causal evidence from pension reform - Niklas Gohl; Peter Haan; Elisabeth Kurz; Felix Weinhardt (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
In this paper we present a life-cycle model with human capital investment during working life through training and provide a novel empirical test of human capital theory. Using a sizable pension reform which shifts the retirement age between two adjacent cohorts by three years, we document causal evidence that an increase in the working life increases investment into human capital through training. We estimate this effect using a regression discontinuity design based on a large sample from the German microcensus. We discuss and test further predictions regarding the relation between initial schooling, training, and the reform effect and show that only individuals with a college degree increase human capital investment. Our results speak to a large class of human capital models as well as policies extending or shortening working life.
Keywords: J24; J26; H21; 330; human capital; retirement policies; RDD